Human Immunodeficiency Virus as a Chronic Disease: Evaluation and Management of Nonacquired Immune Deficiency Syndrome-Defining Conditions. (12th May 2016) - Serrano-Villar, Sergio; Gutiérrez, Félix; Miralles, Celia; Berenguer, Juan; Rivero, Antonio; Martínez, Esteban; Moreno, Santiago
Abstract : The median age of HIV-infected adults on ART is progressively increasing, and most of the issues for HIV specialists involve the follow-up of stable patients and screening, prevention and treatment of age-related conditions. Clinical paradigms of long-term treated HIV infected patients are evolving and warrant incorporation of geriatric principles and expertise in prevention and management of cardiovascular disease, cancer screening and other comorbidities. Abstract: In the modern antiretroviral therapy (ART) era, motivated people living with human immunodeficiency virus (HIV) who have access to therapy are expected to maintain viral suppression indefinitely and to receive treatment for decades. Hence, the current clinical scenario has dramatically shifted since the early 1980s, from treatment and prevention of opportunistic infections and palliative care to a new scenario in which most HIV specialists focus on HIV primary care, ie, the follow up of stable patients, surveillance of long-term toxicities, and screening and prevention of age-related conditions. The median age of HIV-infected adults on ART is progressively increasing. By 2030, 3 of every 4 patients are expected to be aged 50 years or older in many countries, more than 80% will have at least 1 age-related disease, and approximately one third will have at least 3 age-related diseases. Contemporary care of HIV-infected patients is evolving, and questions about how we might monitor and perhaps even treat HIV-infected adults have emerged. Through key published works, this review briefly describes the most prevalent comorbidities and age-associated conditions and highlights the differential features in the HIV-infected population. We also discuss the most critical aspects to be considered in the care of patients with HIV for the management and prevention of age-associated disease.